Depression post stroke in Africa: myth or reality? - (:unkn) unknown (My University, 2014)
Depression is a complication occurring frequently after a stroke. It negatively affects the physical, cognitive and social recovery. Authors report the results of a casecontrol study section was performed in neurology of the friendship hospital and psychiatry of the general hospital in Bangui, from January to August 2012 to ascertain the existence of a link between stroke and depression in hospitalized patients and to identify factors limiting taken into efficient load. On one hundred five subjects included, thirty five were stroke victims matched with seventy witnesses. The prevalence of post stroke depression was 88.6% (31/35) versus (20/70) 28.5% in controls (p <0.001). This post stroke depression occurred in 58% of men with a sex ratio of 1.4. The mean age of subjects with post stroke depression was 49.1 years, with extremes ranging from 33 to 76 years of age. Most (64.5%) subjects with post stroke depression was no occupation; 71.5% of them had a stroke dating back more than six weeks, and 92% had a motor deficit with a Barthel Index <100. Subjects with stroke suffered mostly moderate depression (48.1%) whereas the controls usually had mild depression (80.4%). This depression was not correlated with motor deficit, or the laterality of the lesion, or cognitive disorder. But, some Central African specificities could explain this phenomenon. These results demonstrate the reality of post stroke depression in Africa, hence the need to think in support of any subject with stroke topic. Moreover, questions about the tools used to evaluate the post stroke depression and the time interval between stroke onset and the onset of depressive symptoms remain and require further consideration.
Keywords: African Research